2009
DOI: 10.1111/j.1753-4887.1999.tb06911.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Nutrition to the Health Transition in Developing Countries: A Framework for Research and Intervention

Abstract: The major focus of public health programs in developing populations is alleviating undernutrition. In South Africa, however, as in many other developing countries, the African population is experiencing rapid urbanization characterized by a double burden of disease in which noncommunicable diseases (NCD) become more prevalent and infectious diseases remain undefeated. The possible mechanisms through which nutrition contributes to the additional vulnerability to NCD experienced by developing populations are exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 19 publications
1
38
0
2
Order By: Relevance
“…But on the other hand it has been previously reported that in South Africa the prevalence of CVDs is increasing at an alarming rate in all races 23,24 . This has been partly linked to the nutrition transition the country is undergoing 25 with a shift to a more westernised lifestyle including fatty food and an increase in the intake of fast foods by the South African population 26 .…”
Section: Discussionmentioning
confidence: 99%
“…But on the other hand it has been previously reported that in South Africa the prevalence of CVDs is increasing at an alarming rate in all races 23,24 . This has been partly linked to the nutrition transition the country is undergoing 25 with a shift to a more westernised lifestyle including fatty food and an increase in the intake of fast foods by the South African population 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of early life fetal and infant (low birthweight and stunted children) nutrition deprivation and development of obesity and non-communicable diseases later in childhood or adulthood is still unclear (Popkin, Horton & Kim, 2001;Voster et al, 1999).…”
Section: Early Life Hypothesismentioning
confidence: 99%
“…The epidemiological transition and the concurrent shift in diet, physical activity and body composition in many developing countries have been rapid, unlike the gradual transition in the USA and most European countries (1) . Reports from Asian countries such as Korea, India and Japan, and from countries in South America, indicate that the rapid change in dietary habits and body composition occurred after their countries achieved dietary sufficiency at the national level (2)(3)(4) . In India, the rapid socio-economic transition resulted in rapid changes in dietary patterns (5) .…”
mentioning
confidence: 99%